Branding of Batu Bara Historical Beach as an Effort to Develop a Tourist Destination - Finky, Yollanda; Purba, Rinanda (CV. Publikasi Indonesia, 2024)
This research aims to design an attractive and innovative branding of a beach, the historical beach of Batu Bara is located in Perupuk village, Fifty coastal district, Batu Bara. This historical beach was the first stop and defense of the Japanese army in 1940. However, there are still many people who do not know about the existence of this beach because access to this tourist spot is still quite inadequate, such as poor roads, poor facilities, there is still extortion on this beach, lack of promotional media through social media. For this reason, the purpose of branding Pantai Sejarah Batu Bara is to create an identity, corporate image and awareness of the target audience. Data collection is done through the process of observation and interviews, while the data analysis method used is SWOT analysis and brainstorming and distribution of questionnaires to the public. Effective media in branding this Coal History Beach include handbooks, Instagram feeds, brochures, billboards, merchandise.